2015
DOI: 10.2217/imt.15.47
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine use in Hematopoietic Stem Cell Transplantation: Pharmacokinetic Approach

Abstract: Cyclosporine is one of the most vital agents in the process of successful allogeneic hematopoietic stem cell transplantation. Despite a long history and worldwide extent of cyclosporine use for prevention of graft versus host disease, currently there are lots of uncertainties about its optimal method of application to reach the best clinical outcome. A major portion of this problem stems from complicated cyclosporine pharmacokinetics. Study of cyclosporine pharmacokinetic behavior can significantly help recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 182 publications
0
20
0
Order By: Relevance
“…Given the narrow therapeutic index, it may need routine therapeutic monitoring in case of the transplant rejection and toxic reaction. [30,31] It may frequently co-administered with many compound preparations including active ingredient BG for exerting antihepatitis, anti-inflammatory and antiviral effects. [32,33] A clear and detailed understanding of their propensity for drug-drug interactions (DDIs) is required before their concomitant use in transplantation population.…”
Section: Discussionmentioning
confidence: 99%
“…Given the narrow therapeutic index, it may need routine therapeutic monitoring in case of the transplant rejection and toxic reaction. [30,31] It may frequently co-administered with many compound preparations including active ingredient BG for exerting antihepatitis, anti-inflammatory and antiviral effects. [32,33] A clear and detailed understanding of their propensity for drug-drug interactions (DDIs) is required before their concomitant use in transplantation population.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophilins are a family of proteins present in vertebrates and other organisms. They bind to CsA, an immunosuppressant that is commonly used to suppress rejection after organ transplantation ( 19 20 ). The molecular mechanisms of CsA-induced β cell apoptosis probably involve the downregulation of cyclophilins.…”
Section: Discussionmentioning
confidence: 99%
“…Citterio et al have shown that AUC monitoring would be a better predictor of clinical outcomes in HSCT, while other trials did not find an association between AUC and clinical outcomes . At present, numerous monitoring methods have been proposed in the literature, but unfortunately, there is no consensus for the best practice in the HSCT field …”
Section: Discussionmentioning
confidence: 99%